perceptions and experiences of teachers and students towards the role of artificial intelligence (AI) in promoting self-learning; It is a field research at Koya University - أنور, الأستاذة المساعدة بسيدة حيدر أنور; محمود, الأستاذ المساعد داستان عمر; رمضان, م.م. حازم علي (Sulaimani Journal for Humanities, 2025)
The aim of this research is to explore the perceptions and experiences of teachers and students regarding the role of artificial intelligence (AI) in promoting self-learning. The study population consisted of teachers and students from the Faculty of Education at Koya University. To achieve the research objectives, a mixed-method approach was employed. Qualitative data were collected through interviews with 12 teachers, while the quantitative component was conducted using a descriptive survey method. For this purpose, a 24-item scale was developed, tested for validity and reliability, and subsequently administered to a stratified random sample of 283 students, selected based on stage and gender. Data were analyzed using (SPSS). The Conclusion indicate that participating teachers demonstrated a solid understanding of AI applications in education. Students, on the other hand, reported using AI primarily to clarify difficult topics, access learning resources, and prepare reports and seminar papers. Interviews with teachers revealed a consensus that AI tools can play a significant role in enhancing the learning process and fostering self-learning, provided that students first receive proper guidance in their effective use. Students perceived AI tools as having a moderate impact on improving both general learning and self-learning. Furthermore, the variables of gender and educational level did not show a significant effect on the role of AI in promoting learning and self-learning.
Keywords: Artificial intelligence; education; self learning; university students; AI